Nucleotide sequence of the ribosomal protein gene cluster adjacent to the gene for RNA polymerase subunit beta in Escherichia coli. - Post, L E (1979)
The 3072-nucleotide-long sequence of a segment from the 88-min region of the Escherichia coli chromosome has been determined. The sequence covers the genes for ribosomal proteins L11 (rplK), LI (rplA), L10 (rplJ), and L7/L12 ((rplL), and the 5' end of the gene for the beta subunit of RNA polymerase (rpoB), along with the presumed regulatory regions for these genes. The probable locations of the promoter for the first two genes (the L11 operon) and the promoter for the latter three genes (the proximal part of the beta operon) have been identified. We have also found that the four ribosomal protein genes preferentially use codons that are recognized efficiently by the most abundant tRNA species. These and other features of the sequence results are discussed in relation to available information obtained from both in vitro and in vivo experiments on the expression of these ribosomal and RNA polymerase subunit genes.